Some observations on the law applicable to the determination of natural filiation (art. 9.4.I Cc): analysis of the Valencia SAP of June 26 - Sánchez Cano, María Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
In our country, the rule governing the law applicable to the determination of natural filiation is Art. 9.4 Cc. It is a materially oriented conflict rule that is structured by means of multiple hierarchical or cascading connection points. In practice, problems arise in establishing the scope of application of the law designated by Art. 9.4 Cc and, in particular, in establishing the matters to which this provision refers. This paper will analyse the solutions that the Valencia SAP nº 414/24, of 26 June, proposes to the disadvantages generated by the application in practice of Art. 9.4.I Cc, taking into account the most relevant doctrine and jurisprudence.
Keywords: Natural filiation; art.9.4 Cc; applicable law; International Private Law